2018
DOI: 10.1017/s0950268818000298
|View full text |Cite
|
Sign up to set email alerts
|

Association between TLR2 + 2477G/A polymorphism and bacterial meningitis: a meta-analysis

Abstract: Toll-like receptor 2 (TLR2) is a key member of TLRs, which is crucial in the initial inflammatory response against bacteria. TLR2, is also the initial barrier against bacterial infection and plays an important role in recognising a variety of bacterial lipoproteins. Several studies have been performed to investigate the TLR2 + 2477G/A polymorphism and bacterial meningitis susceptibility. Unfortunately, the results of previous studies were controversial. Therefore, we performed a meta-analysis to derive a more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Genetic polymorphisms vary significantly across different countries and regions, impacted by the distinct racial backgrounds present. [18][19][20][21][22][23][24] Our research focuses on the Chinese population, whose genetic polymorphisms differ from those observed in Egypt and Saudi Arabia. Given that Egypt is in North Africa and Saudi Arabia is in West Asia, their genetic profiles are markedly different from those of the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms vary significantly across different countries and regions, impacted by the distinct racial backgrounds present. [18][19][20][21][22][23][24] Our research focuses on the Chinese population, whose genetic polymorphisms differ from those observed in Egypt and Saudi Arabia. Given that Egypt is in North Africa and Saudi Arabia is in West Asia, their genetic profiles are markedly different from those of the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of a substantial sample size is crucial for the study of gene polymorphism and has been demonstrated to be beneficial in previous literature. 34 , 35 , 36 , 37 , 38 , 39 , 40 However, there are certain limitations that must be acknowledged. Although our study design was innovative in exploring TNF‐α rs1800629 polymorphism in PNS patients, there is always room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…All methods applying the present meta-analysis were based on published literatures. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] 2.4. Statistical analysis SPSS17, STATA11 software, t test, χ2 test statistic tools were applied in our investigation, as reported by previous literatures.…”
Section: Meta-analysis Processmentioning
confidence: 99%